Total phenolic content and total flavonoid of H.Polyrhizus waste extract by using ultrasonic solvents extraction - Lee, Qiao Hui (2009)
Research in extracting colour from natural fruits has been actively conducted nowadays. In this research, red pitaya peels was selected as a raw material. Red pitaya peels was selected because of red pitaya easily find in local market and its can reduce waste production in the world, which is environmental friendly. This research is to analyze the total phenolic contents and total flavonoids from red pitaya peels. Its also analyze the effect of the different solvents to the production of natural color from red pitaya waste. Four different solvents: n-hexane, ethanol, propanol and acetone has been used in extracting total phenolic contents and total flavonoid from red pitaya waste. Three different parameter of ultrasonic extractor (25, 68, 132 kHz) were used in extracting red pitaya peels with four solvents respectively. The analysis was conducted in University Malaysia Pahang laboratory using the ultraviolet-visible spectrophotometry. Most important step in this research is the analysis of total phenolic and total flovonoid contents for twelve samples. Based on the result of this research, the best solvent for total phenolics and flavonoids from red pitaya waste is ethanol, followed by propanol and acetone. This is due to the highest polarity of ethanol. On the other hand, n-hexane extracts show the lowest total phenolic and flavonoids contents. 132kHz ultrasonic extractor extracts more total phenolic and flavonoids contents, follow by 68kHz and 25kHz ultrasonic extractor. As a conclusion, the highest polarity of the solvents and frequency extract more color pigments, total phenolic and flavonoids from red pitaya waste.